(untitled) (Sudurpaschim Spectrum, 2026)
This study examines the impact of remittance utilization on the socioeconomic development of community people in Birendranagar 14, Surkhet. With foreign employment becoming a major livelihood option for many households in Nepal, remittances have emerged as a vital source of income. The primary objective of this research is to analyze how remittance income influences various aspects of socioeconomic development, including education, healthcare, housing, and daily living standards. To fulfill this objective, a quantitative research approach was employed. Primary data was collected through structured household surveys, conducted among 63 randomly selected families of Ward No. 14. The survey questionnaire focused on remittance sources, utilization patterns, and the perceived impact on the community’s standard of living. The findings show that remittances significantly contribute to improving the quality of life of migrant families. However, the study also identifies several challenges in the effective use of these funds, such as poor financial literacy, lack of investment planning, limited local opportunities, and inadequate government support. In many cases, remittance income is spent on consumption rather than being invested in productive sectors, which limits its long-term impact on local development. By addressing these challenges and promoting better utilization practices, remittances can be a powerful tool for sustainable socioeconomic growth in the region. This research provides valuable insights for policymakers, development planners, and community leaders aiming to harness remittance for local development.